Reaction of Cells Desmodesmus armatus (Chod.) Hegew. on the Induction of Carotynogenesis - Чебан, Лариса (My University, 2018)
Various studies of the components of the antioxidant protection system of microalgae D. armatus under the influence of osmotic stress and active forms of oxygen will allow to develop methods for controlling carotenogenesis in a given culture and to obtain carotenoid enriched feed for zooplankton. These studies made it possible to evaluate the activity of catalase, peroxidase enzymes in cells that are cultured under the induction of carotenogenesis by free radical oxidation promoters and osmotic stress on the background of physiological changes. It is established that under these conditions, there is an increase in volumes and aggregation of vegetative cells. At the same time, the amount of biomass remains at the level of the first day of inductors application. Against the background of a decrease in growth activity, a decrease in the number of metabolically active cells in cytochrome oxidase was observed. It is also shown that, when iron sulfate is introduced with hydrogen peroxide and sodium chloride against the background of enhanced carotenogenesis, antioxidant systems are activated by increasing the activity of catalase and peroxidase. Under such conditions, it is possible to achieve increased production of carotenoids in Desmodesmus armatus culture.
Keywords: carotenogenesis; Desmodesmus armatus; cytochrome oxidase; catalase; peroxidase